Arthrogryposis multiplex congenita: Part 1: Clinical and electromyographic aspects - Bharucha, E. P. (1972)
Sixteen cases with arthrogryposis multiplex congenita were examined clinically and electromyographically; three of them were re-examined later. Joint deformities were present in all extremities in 13 of the cases; in eight there was some degree of mental retardation. In two cases, there was clinical and electromyographic evidence of a myopathic disorder. In the majority, the appearances of the shoulder-neck region suggested a developmental defect. At the same time, selective weakness of muscles innervated by C5-C6 segments suggested a neuropathic disturbance. EMG revealed, in eight of 13 cases, clear evidence of denervation of muscles, but without any regenerative activity. The non-progressive nature of this disorder and capacity for improvement in muscle bulk and power suggest that denervation alone cannot explain the process. Re-examination of three patients after two to three years revealed persistence of the major deformities and muscle weakness noted earlier, with no appreciable deterioration.